"Crowd logistics": the contribution of social crowds in logistics activities. Issue 3 (15th August 2016) - Mladenow, Andreas; Bauer, Christine; Strauss, Christine
Abstract : Purpose: The paper aims to provide the necessary basis for a novel interdisciplinary research field. Various types and implementations of crowdsourcing have emerged in the market; many of them are related to logistics. While we can identify plenty of crowd logistics applications using information technology capabilities and information sharing in practice, theories behind this phenomenon have received only limited attention. This paper accounts for filling this research gap by analyzing the crowd's contributions in logistics of goods and information. Design/methodology/approach: This paper is part of an ongoing research endeavor in the field of location-based crowdsourcing. It represents conceptual work that builds on a literature review enriched with an in-depth analysis of real-world examples in the field of crowd logistics. Using a scoring method, we provide an example how a company may evaluate the alternatives of crowd logistics. The main approach is an analysis of variants of how the social crowd may be integrated in logistics processes. The work is conceptual in its core. Thereby, we use real-world examples of crowdsourcing applications to underpin the evaluated variants of crowd logistics. Findings: The paper presents relevant theoretical background on crowd logistics. The authors differentiate between variants of crowd logistics with their flow of materials, goods and information. Thereby they zoom in the type, significance and process flow of the crowd's contributions. They discuss potential advantages and challenges of logistics with the performing crowd and deeply discuss opportunities and challenges from a business and from an individual's perspective. Finally, they highlight a route map for future research directions in this novel interdisciplinary research field. Research limitations/implications: As this work is conceptual in its core, generalizations may be drawn only with great care. Still, we are in a position to propose a route map for further research in this area in this paper. Also the integration of an analysis of a scale of real-world applications allows us to highlight our research's practical relevance and implications. Originality/value: The main contribution of this paper is an in-depth analysis and consolidation of innovative crowd logistics applications to provide an overview on recent implementations. The authors propose a categorization scheme and contribute with a route map for further research in the field of crowd logistics.